Manajemen Sumber Daya Manusia (Guru) dalam Meningkatkan Mutu Pembelajaran Tahfidz Qur'an di SDIT Al-Fitrah - Yunita, Arinda; Supendi, Pepen (BISMA : Business and Management Journal, 2024)
This research explores teacher resource management in improving the quality of tahfidzul Qur’an learning at the Al-Fitrah Integrated Islamic Elementary School (SDIT). Human resource management (HR) refers to the management and development of employees in an organisation, including in the educational context, where teachers are a key element who act as facilitators and inspirers for students. Teacher human resources are educators who have the responsibility to educate, guide and develop the potential of students. The objectives of this research are: 1). to find out how the HR management process for SDIT Al-Fitrah teachers is, 2). to find out how to implement HR management at SDIT Al-Fitrah school, 3). to find out the strategy for improving the quality of human resources at SDIT Al-Fitrah. The research results show that planning focuses on the qualifications of tahfidz teachers and activities designed to improve the quality of teaching. Implementation includes recruitment, selection, training and performance assessment of tahfidz teachers. Finally, the results of this management succeeded in improving the quality of tahfidzul Qur'an learning at SDIT Al-Fitrah.